Comparison of Double Exponential Smoothing and Double Moving Average for Forecasting Lost Vehicle Registration Certificates in Pamekasan - Ramadani, Nia; Faisol; Kuzairi; Amalia, Rica (Contemporary Mathematics and Applications (ConMathA), 2025)
The government issues the Vehicle Registration Certificate (STNK), an official document that certifies a motorized vehicle's identity and authenticity. Pamekasan Regency is one of the regencies in East Java Province that frequently suffers losses associated with Vehicle Registration Certificates (STNK). Consequently, it is essential to predict the amount of car registration losses so that the Pamekasan regional administration can use the information to lower the losses. The Double Exponential Smoothing and Double Moving Average techniques were used in this study to forecast the amount of vehicle registration losses. According to the research findings, the smoothing parameters ? = 0.3 and ? = 0.025 had the lowest MAPE value from the Double Exponential Smoothing method, with a MAPE value of 49.4082%. The double moving average method's smallest MAPE, ? = 3, has a MAPE value of 31.53215%. The twofold moving average approach is the best way to forecast the loss of car registration in Pamekasan, according to the comparison's findings.